Odpowiedzi

2009-11-12T19:54:39+01:00
(2a-3b)+(4a-b)=2a-3b+4a-b=6a-4b

-(x\2-3x)+(x/2+3x)=-x²+3x+x²+3x=6x

(a+b-c)-(2a-b+2c)=a+b-c-2a+b-2c=-a+2b-3c

-(x/2-xy-z)-(-x/2+2xy+2z)=-x²+xy+z+x²-2xy-2z=-xy-z
Najlepsza Odpowiedź!
2009-11-12T19:58:14+01:00
1) =2a -3b+4a-b=6a-4b
2) = -x² +3x+ x² +3x =6x
3) =a+b-c-2a+b-2c= -a+2b-3c
4) =-x² +xy +z-x²-2xy-2z= -2x² -xy -z
  • tos
  • Początkujący
2009-11-12T20:23:34+01:00
1) (2a-3b)+(4a-b)=8a\2+2ab-12ab-3b\2
2) -(x\2-3x)+(x\2+3x)=-x\4-3x\3+3x\3=9x\2
3) (a+b+c)-(2a-b+2c)=2a\2-ab+2ac+2ab-b\2+2bc-2ac+bc+2c\2=2a\2+ab-b\2+3bc+2c\2
4) -(x\2-xy-z)-(-x\2+2xy